ORINOCO CROCODILE CROCODYLUS INTERMEDIUS (1992)
The Orinoco crocodile is a large, relatively long-nosed crocodile restricted to the middle and lower reaches of the Orinoco River and its tributaries in Venezuela and Colombia Although this crocodile was found in a wide variety of habitats, including rivers in tropical evergreen forest and piedmont streams in the foothills of the Andes, it reached its greatest numbers in the seasonal rivers of the Llanos savanna region